Factors of social media promotions affecting consumer purchase decisions toward baked goods in Iloilo - Gallano, Jerry Mae B.
Social media has been the routine in promoting businesses online to appeal to consumers. Many researches studied the relationships between related concepts such as purchase decisions and factors of social media marketing, however, present literature studied all the marketing mix, including product, price, place, and promotions. The main purpose of the study is to characterize baked goods consumers in Iloilo who use Facebook and Instagram. It is also intended to determine which factors of socila media promotions strongly influence consumer purchase decisions. Quantitative approach is used in conducting the study. Analysis of the consumer prchase decision is based on numerical data from the survey. In conducting this research study, a correlational research design is employed. This study uses non-probability and purposive sampling in consideration of the limitations in resources, and the persisting global health crisis. The sample consists of 201 respondents among ages 15-40. A researcher-made questionnaire is used in gathering the data through google forms. Results of the Spearman correlation analysis revealed that all the independent. variables namely: promotional material aesthetics, sales promotions, frequency of posting, and electronic word of mouth significantly affect consumer purchase decisions. It is imperative for business to craft strategies in improving visual elements, sales promotions in the form of short-term offers like discounts, price-offs, regular and consistent posting of promotional materials, and electronic word of mouth, as these factors are influential to the purchase decisions of Iloilo baked goods consumers.